How adapted are built-environment professionals to flood adaptation?. Issue 4 (29th August 2019) - Hobeica, Liliane; Hobeica, Adib
Abstract : Purpose: The purpose of this paper is to explore how architectural practices have been considering flood-risk adaptation within regular design activities. It relies on the assumptions that floods are hybrid phenomena that require actions in both the anthropic and hydrological domains to be successfully managed, and that floods' spatial dimension can be subject to design to minimize the impacts of disasters. Design/methodology/approach: This paper draws on the conclusions of a research focussing on the design of flood-prone urban projects in Europe, within which 22 built-environment professionals (BEPs) were interviewed. The statements of these informants were examined through content analysis, as a means to reveal barriers and incentives that affect their perception and practice of dealing with floods through design. Findings: Having different experiences with flood-related projects, the interviewees showed uneven degrees of sensitivity to manage floods through design. The analyses pinpoint that for BEPs to be up to the challenges associated with these projects, besides technical expertise, some soft skills are needed such as professional openness and a positive mindset. Originality/value: This paper explores flood adaptation not only as a spatial challenge but also as a cultural change that needs to be embraced within flood risk management efforts.